Challenges for the EU-China BIT negotiations - Yong Liang (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
The EU-China Summit Joint Statement in April 2019 set an ambitious target for the conclusion of an EU-China Comprehensive Investment Agreement in 2020. However, some critical concerns remain to be addressed. This Perspective discusses market access, national treatment, investment court system and "investment-plus" and "investment-extra" issues and gives some suggestions.
Keywords: 330